Efektivitas vitamin C dan ekstrak temulawak terhadap kelangsungan hidup dan pertumbuhan ikan nila (Oreochromis niloticus): The effectiveness of vitamin c and curcuma extract against survival rate and growth of the tilapia (oreochromis niloticus) - Siswanto; Mustaqiim Pangestu (Universitas Sam Ratulangi, 2023)
This study aimed to find out the effects of combination of feed additives in the form of curcuma and vitamin C on the survival rate and growth of tilapia fries. The feed used was commercial feed with protein content of ±33%. The source of vitamin C was IP 50mg of 150mg/kg of feed while curcuma extract was obtained from the rhizome of curcuma extracted by 6g of dry weight/kg of feed. The experimental design used a complete randomized design (RAL), consisted of 3 treatments and 3 repeats. Treatment A= Commercial feed by added vitamin C and curcuma extract, B= Commercial feed by added vitamin C and treatment C= Commercial feed without added feed additives. The observed parameters were survival rate (SR), relative growth rate (RGRW), relative total length (RGRL) and water quality. The survival value of the highest in a row was treatment B with a value of 96.67±5.77%, treatment A with a value of 93.33±11.55% followed by treatment C with a value of 80.00±17.32%. The relative growth rate of the highest was treatment B (6.38±2.54%), treatment A (6.25±1.62%) followed by treatment C (4.92±1.66%). For the relative total length value was treatment B (1.21±0.39%), treatment A (1.14±0.26%) followed by treatment C (1.00±0.22%). Keywords: Vitamin C, curcuma, survival rate, growth, tilapia fries.